2005
DOI: 10.1160/th05-05-0338
|View full text |Cite
|
Sign up to set email alerts
|

An optimized embryonic stem cell model for consistent gene expression and developmental studies

Abstract: SummaryIn vitro differentiation of embryonic stem(ES) cells results in generation of tissue-specific somaticc ells and mayr epresent a powerful tool forg eneral understandingo fc ellular differentiation and development in vivo.Culturing of most ES cell lines requires murinee mbryonicf ibroblasts (MEF),w hich mayi nfluence adventitiously the genetic differentiation programofES cells.We compared the expression profile of keydevelopmental genesinthe MEF-independentCGR8EScellline and in the MEFdependentD 3E Sc ell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…CGR8 ESCs (ECACC 95011018) were cultured without feeder cells in Glasgow minimum essential medium supplemented with 10% fetal bovine serum (FBS), 2 mM lglutamine, 100 U/mL LIF, and 50 mM b-mercaptoethanol (ME) in 0.2% gelatine-coated flasks as previously described [10]. CGR8 ESCs (passage No.…”
Section: Esc Culture and Eb Formationmentioning
confidence: 99%
“…CGR8 ESCs (ECACC 95011018) were cultured without feeder cells in Glasgow minimum essential medium supplemented with 10% fetal bovine serum (FBS), 2 mM lglutamine, 100 U/mL LIF, and 50 mM b-mercaptoethanol (ME) in 0.2% gelatine-coated flasks as previously described [10]. CGR8 ESCs (passage No.…”
Section: Esc Culture and Eb Formationmentioning
confidence: 99%
“…The murine embryonic stem cell line CGR8 was a generous gift from Dr. J. Hescheler, University of Cologne, Germany (Gissel et al, 2005). Undifferentiated cells were cultured under standard conditions in gelatinized flasks with Glasgow's buffered minimal essential medium (Gibco, Germany), supplemented with 100 U/ml leukaemia inhibitory factor (LIF; Sigma Aldrich, Germany) to maintain pluripotency.…”
Section: Cgr8 Cellsmentioning
confidence: 99%
“…3 we selected four spots, 8,9,36 commercial antibodies are available for quantification on Westernblot filters. Fig.…”
Section: Cardiospheres and Their Protein Profiling By 2-d Sds-pagementioning
confidence: 99%
“…For regenerative medicine, an understanding of the regulatory molecular mechanism for cell differentiation and self-replenish is crucial. Towards achieving this goal, gene expression analyses with transcription profiling (transcriptome) and micro-arrays have been conducted including neurospheres [7], mouse and human embryonic stem cells [8,9,10] and left atrium derived stem cells [11]. These mRNA analyses, however, have limitations because several investigations revealed that protein expression levels correlated poorly with mRNA level due to the multiple regulatory factors including mRNA stability, rate of translation and protein degradation [12,13].…”
Section: Introductionmentioning
confidence: 99%